Mechanics of responsive polymers via conformationally switchable molecules. (April 2018) - Brighenti, Roberto; Artoni, Federico; Vernerey, Franck; Torelli, Martina; Pedrini, Alessandro; Domenichelli, Ilaria; Dalcanale, Enrico
Highlights: Reactive polymers containing switchable molecules are considered. Conformation switching produce a macroscopically detectable deformation of the polymer. Molecule conformation switching is triggered by chemical or mechanical stimuli. A theoretical micromechanics-based model is proposed. PDMS elastomer with quinoxaline cavitands molecules under chemical stimuli is tested experimentally. Numerical tests are performed. Abstract: Active materials are those capable of giving some physical reaction under external stimuli coming from the environment such as temperature, pH, light, mechanical stress, etc. Reactive polymeric materials can be obtained through the introduction of switchable molecules in their network, i.e. molecules having two distinct stable conformations: if properly linked to the hosting polymer chains, the switching from one state to the other can promote a mechanical reaction of the material, detectable at the macroscale, and thus enables us to tune the response according to a desired functionality. In the present paper, the main aspects of the mechanical behavior of polymeric materials with embedded switchable molecules—properly linked to the polymer's chains—are presented and discussed. Starting from the micro mechanisms occurring in such active material, a continuum model is developed, providing a straightforward implementation in computational approaches. Finally, some experimental outcomes related to a switchable molecules (known as quinoxaline cavitands) added to an elastomeric PDMS under chemical stimuli, are presented and quantitatively discussed through the use of the developed mechanical framework.